2021
DOI: 10.1111/lam.13488
|View full text |Cite
|
Sign up to set email alerts
|

Insights into collateral susceptibility and collateral resistance in Acinetobacter baumannii during antimicrobial adaptation

Abstract: Significance and Impact of the Study: Acinetobacter baumannii exposed to one antibiotic could exhibit various susceptibility to other antibiotic treatments. The polymyxin B (PMB)-adapted A. baumannii showed distinct phenotypic adaptation related to the collateral susceptibility and collateral resistance. This study highlights the development of collateral susceptibility and collateral resistance in A. baumannii exposed to various antibiotic treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…2017; Dawan et al . 2021), no report has observed the same phenomenon using natural compounds except one case study (Bischofberger et al . 2021).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…2017; Dawan et al . 2021), no report has observed the same phenomenon using natural compounds except one case study (Bischofberger et al . 2021).…”
Section: Resultsmentioning
confidence: 90%
“…The sensitization and re-sensitization of resistant bacteria to antibiotics and other stresses have been observed early, involving weakening or interrupting bacterial defense mechanisms (Repaske 1958;Vaara and Vaara 1983;Helander et al 2001). While the collateral sensitivity of bacteria to an antibiotic was found to develop during the adaptation of the bacteria to other types of antimicrobial drugs (Barbosa et al 2017;Dawan et al 2021), no report has observed the same phenomenon using natural compounds except one case study (Bischofberger et al 2021). The collateral sensitivity is theoretically feasible and might direct the evolution trajectories and counteract the antibiotic-resistant mechanisms (Rodriguez de Evgrafov et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the single–drug–treated lineages collected in this study adapted to the antibiotics (CIP and PMB) without mutation [ 44 ]. Consequently, the collateral susceptibility observed in this study can be attributed to the pre–adaptation phenomenon, which has been found to be associated with beta–lactamase and efflux pump activities [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%